Mobile Devices in Student Learning: Enhancing Engagement or Contributing to Distractions? - Attah, Emmanuel Yusuf; Lamidi, Kehinde Felix; Santas, Tsyegu; Edino, Ferdinand Ojonimi (Journal of Education Method and Learning Strategy, 2025)
Integrating mobile devices into educational settings has reshaped traditional learning environments, offering both opportunities and challenges. This study aims to investigate the role of mobile devices in enhancing student engagement, academic performance, and overall learning outcomes. The major objectives include examining the benefits and drawbacks of mobile device use in education, identifying effective strategies for managing mobile device integration, and understanding its impact on student focus and motivation. A quantitative research design was employed, with data collected through surveys from students in various educational institutions. The findings indicate that while mobile devices enhance access to educational resources, promote collaboration, and increase student engagement, they also contribute to distractions and cognitive overload, affecting academic performance. Case studies, such as the University of Maryland’s mobile learning initiative and the "One Tablet per Student" program in Uruguay, provide insights into the practical challenges of integrating mobile technology in education. The study recommends, among others, that educators strike a balance between leveraging technologies for academic purposes and managing the distractions they may cause to ensure the effective use of mobile devices in enhancing educational outcomes.